Standardization of Formulation for Development of Ginger Supplemented Confectionary Products - Kaushal, Manisha; Vaidya, Devina; Kaushik, Ranjan; Aarti; Verma, Anil; Gupta, Anil (International Journal of Bio-resource and Stress Management, 2018)
Indian confectionery is one of the fastest growing sectors in the world with an estimated growth rate of 18–20% where India ranks 14th globally. Today, with modern technology and continued growing interest in these products, large companies are competing to come up with the most interesting and novel products in the market. Ginger has a long history of use as a remedy and medicinal purposes due to its therapeutic and functional properties which were harnessed for the development of ginger appetizing tablets (gingoli) and ginger fruit bar. Gingoli was prepared by the wet granulation method, where the organoleptic acceptable formulation contained 25 g ginger powder in the standardized recipe with pear pak as binding agent. The granular formulation of ginger powder had characteristics preferable for tablet formation with Carr compressibility of 12.28%, Hausner ratio 1.14 and an angle of repose as 27°. Further, among the different formulations for the development of ginger fruit appetized bar, ginger: plum 50:50 with 1.5% appetizing mixture had highest acceptability scores with the dehydration ratio observed as 3.48:1 and moisture content of 12.64%. Further, the supplementation of ginger for the preparation of ginger appetizing tablets and ginger fruit bar possessed significantly higher antioxidant activity, total phenols and crude fibre thus enhancing its functional properties and potentiality for market acceptability.